Expressão de fatores miogênicos e de microRNAs no músculo esqueléticos de ratos submetidos a estímulo atrófico e recuperação por treinamento físico - Bertaglia, Raquel Santilone [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Understanding the cellular and molecular mechanisms involved in hypertrophy and atrophy processes have been the subject of much research. This fact contributes to development of effective therapeutic strategies to attenuate/block the muscle mass loss. However, myogenic factors and muscle-specific miRNAs have been studied to understand the skeletal muscle adaptive responses. The aim of this study were to evaluate the morphological and functional adaptations, the gene expression of myogenic, anabolic and catabolic factor, and the expression of microRNAs in skeletal muscle of rats submitted to atrophic stimulus followed by physical training. 80 male Wistar rats were used (80 days 250 to 300 g) were divided into 10 groups (n = 8) C: Control; IM: immobilizated; C3: control 3 days; R3: recovered without exercise 3 days; T3: aerobic training 3 days; TF3: strength training 3 days; C7: control 7 days; R7: recovered without exercise 7 days; T7: aerobic training 7 days and TF7: strength training 7 days. Initially, the animals of I, R3, R7, T3, T7, TF3 and TF7 groups were underwent period of hindlimb immobilization by 7 day. Plantaris (Pl - glycolytic and fast twitch) and soleus (Sol - oxidative and slow twitch) muscles were analyzed. Muscle atrophy was confirmed by the analysis of cross-sectional area (CSA) of fibers in groups I and C. The T3 and T7 groups, were underwent a muscle recovery program with aerobic exercise (swimming) 3 period and 7 days respectively while the TF3 and TF7 groups were underwent a muscle recovery program with resistance exercise (jump). At the end of experiment the Pl and Sol muscles were submitted to analysis: morphological, immunohistochemical, biochemical and molecular. Muscle atrophy was observed in both muscles after immobilization, but after 7 days of recovery, only the T7 group showed recovery in CSA. Gene expression data showed: increase in genes involved in muscle atrophy in group I in Sol (MAFbx, PGC-1α and ...

O entendimento dos mecanismos celulares e moleculares envolvidos com os processos de hipertrofia e atrofia muscular têm sido alvo de muitas pesquisas. Tal fato contribui para desenvolvimento de estratégias terapêuticas eficazes para atenuar ou até mesmo bloquear a perda de massa muscular. Neste contexto, fatores miogênicos e microRNAs (miRNAs) têm sido estudados para melhor compreender as respostas adaptativas do músculo esquelético. Os objetivos do presente trabalho foram avaliar as adaptações morfofuncionais, a expressão gênica de fatores miogênicos, anabólicos e catabólicos e a expressão dos miRNAs no músculo esquelético de ratos submetidos à estimulo atrófico, seguido de treinamento físico, aeróbico e resistido. Foram utilizados 80 ratos Wistar machos (80 dias, 250 a 300 g), divididos em 10 grupos (n=8): C: controle; I: imobilizado; C3: controle 3 dias; R3: recuperado sem exercício 3 dias; T3: treinamento aeróbico 3 dias; TF3: treinamento de força 3 dias; C7: controle 7 dias; R7: recuperado sem exercício 7 dias; T7: treinamento aeróbico 7 dias e TF7: treinamento de força 7 dias. Inicialmente, os animais dos grupos I, R3, R7, T3, T7, TF3 e TF7 foram submetidos a um período de 7 dias de imobilização dos membros posteriores. Foram analisados os músculos plantar (Pl - glicolítico e de contração rápida) e sóleo (Sol - oxidativo e de contração lenta). A atrofia muscular foi confirmada pela análise da área de secção transversal (AST) das fibras nos animais dos grupos I e C. Os grupos T3 e T7, foram submetidos a um programa de recuperação muscular com exercício aeróbico (natação) no período de 3 e 7 dias respectivamente enquanto os grupos TF3 e TF7 foram submetidos a um programa de recuperação muscular com exercício resistido (salto). Ao término do experimento os músculos Pl e Sol foram submetidos às análises: morfológica, histoquímica, bioquímica e molecular. Observamos atrofia muscular em...
Keywords: Atrofia muscular; Aptidão física; Sistema musculoesquelético; Seqüenciamento de nucleotídeo; Expressão gênica; Physical fitness; Musculoskeletal system